Development of android based augmented reality video for tennis courts learning - Sulaksono, Galang (Journal Sport Area, 2021)
This research aims to develop an android-based augmented reality application called AR Tennis. The resulted product is used as a medium for learning tennis courts courses. The AR Tennis application helps students understand the illustrations contained in courts tennis textbooks. The picture in the book which is originally only a silent illustration, with the help of the AR Tennis application, the image will move. The method used is MDLC (Multimedia Development Life Cycle). Testing the application using the blackbox method and the results are all components of the application function properly. From the results of the assessment of learning media experts obtained a value of 97.6 with a very good category. From the expert on tennis material, the score is 89.2 with a good category. And trials for students who take part in tennis court scored 92.14 in the appropriate category for use. Augmented reality technology is still not popular in the field of education. But going forward this technology will be very helpful in any study in the education.